Reproductive endocrine disruption in the freshwater catfish, Heteropneustes fossilis, in response to the pesticide ¿-hexachlorocyclohexane - Singh, Pratap B. (2014)
Both male and female freshwater catfish, Heteropneustes fossilis, were exposed to safe (SC; 0.1 and 1.0 mg/L) and sublethal (SL; 10 mg/L) concentrationsof an agricultural pesticide, g-hexachlorocyclohexane (g-HCH) for 4 weeksduring the active pre-spawning (vitellogenic) phase of their annual reproductive cycle. On the last day of exposure, 18 h before killing, fish were treated intramuscularly (i.m.) with [I-14C]acetic acid (74 kBq per fish). After 4 weeks of exposure, we monitored the effects of g-HCH on gonadosomatic index (GSI); on plasma concentrations of gonadotropin (GtH), testostosterone (T), 11-ketotestosterone (11-KT), 17b-estradiol (E2); and on hepatic incorporation of [I-14C]acetic acid into total phospholipids (TP) and the fractions thereof: phosphatidylcholine (PC), phosphatidylserine (PS), phosphatidylinositol (PI), and phosphatidylethanolamine (PE). In both the sexes, GSI and plasma GtH were decreased significantly in response to g-HCH exposure. Plasma T and 11-KT in males, and plasma T and E2 in females declined significantly in response to g-HCH exposure. In both the sexes, hepatic incorporation of [I-14C]acetic acid into PS and PI increased significantly, whereas incorporation into TP, PC, and PE was significantly reduced after g-HCH exposure. Our findings demonstrated that g-HCH exposure depressed GSI, plasma GtH, sex steroids, and [I-14C]acetic acid incorporation into hepatic TP, and had very selective and specific effects on various classes of TP, resulting either from the hypothalamo-hypophyseal-gonadal axis or from direct action on hepatic and steroidogenic enzymes during the pre-spawning phase, causing reproductive endocrine disruptions.